MEMBERSHIP PAGE. - Sawin, Gregory (ETC: A Review of General Semantics)
The article provides information on author and lecturer Risa Kaparo's October 2000 visit to China to give a lecture on Somalogics, a medical research system, and also provides a personal narrative in which the author discusses his application of general semantics to his career in computer programming.